Placental massive perivillous fibrinoid deposition causing severe intrauterine growth restriction - Lacunza Paredes, Rommel Omar (2020)
Placental massive perivillous fibrinoid deposition or maternal floor infarction is a rare entity associated with intrauterine growth restriction, fetal death and poor perinatal outcome. It is characterized by the perivillous deposition of fibrinoid material, without a clear etiology. We present the first documented case in Peru.